2019
DOI: 10.1039/c9tc05291g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mode structural-color anti-counterfeiting labels based on physically unclonable amorphous photonic structures with convenient artificial intelligence authentication

Abstract: The first physically unclonable anti-counterfeiting label based on structural colors was enabled by interfacing amorphous photonic structures with artificial intelligence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 41 publications
0
90
0
Order By: Relevance
“…The orientation of the short-range ordered crystal is equivalent along all the directions, thereby the coherent light can be uniformly scattered to different viewing angles through the amorphous structures. [63,64] In addition, angle-resolved spectra (Figure 3f,g) of APCs show that the reflection peak of the film was almost unchanged under different viewing angles, further proving the non-iridescent structural color of APCs.…”
Section: Resultsmentioning
confidence: 82%
“…The orientation of the short-range ordered crystal is equivalent along all the directions, thereby the coherent light can be uniformly scattered to different viewing angles through the amorphous structures. [63,64] In addition, angle-resolved spectra (Figure 3f,g) of APCs show that the reflection peak of the film was almost unchanged under different viewing angles, further proving the non-iridescent structural color of APCs.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, researchers have prepared many types of PUF anticounterfeiting labels with optical response. For example, Cheng et al [13] reported a multicolor plasma nanopaper with random Raman intensity distribution, He et al [14] designed multi-mode structural-color anti-counterfeiting labels composed of randomly arranged nanospheres, and Leem et al [15] developed edible silk film labels with random light response. To improve the capabilities and speed of unclonable-pattern recognition,…”
mentioning
confidence: 99%
“…[75][76][77][78][79][80][81][142][143][144] Meanwhile, direct writing indicates that the pattern is directly fabricated without a template, such as inkjet printing, drop-coating and spray-coating. 69,[84][85][86][87][88][89][90][91][92]…”
Section: Preparation Strategies For Pc Patternsmentioning
confidence: 99%
“…[75][76][77][78][79][80][81][82][83] A noniridescent structural colour pattern originates from the breakage of a longrange ordered structure and assembly of a short-range ordered structure. 69,[84][85][86][87][88][89][90][91][92][93][94] Various processes are used for the preparation of short-range ordered structures for noniridescent structural colour patterns, such as spraying a mixture of two differentsized particles, 95 atomization deposition of a silica nanoparticle dispersion accompanied by an additive, poly(vinyl alcohol) (PVA), 24 and stretching the composite film to form short-range ordered nanovoids in the local strain region. 22 Particularly, adding black matter (such as graphene or cuttlefish ink particles) to the amorphous structure is beneficial for yielding bright, highly saturated and brilliant noniridescent structural colour patterns.…”
Section: Introductionmentioning
confidence: 99%